The Habeas Data, protection to the right of information and informational Self- Determination - Quiroz Papa de García, Rosalía (2016)
The research describes and analyses the level of protection of the right of access to information and protection of personal data or informational self-determination, through the jurisprudence of Habeas Data determined by the Constitutional Court of Peru during the last five years (2010-2014). It identifies the places of highest incidences of this type of guarantee, types of plaintiffs and defendants, the matter of demand and the type decisions issued by the Court that ended to the demands of Habeas Data.